Asymptomatic Permanent Left Bundle Branch Block (LBBB) complicating Diagnostic Left Heart Catheterisation - Hafidh Al-Hadi; Mansour Sallam (Sultan Qaboos University Medical Journal, 2010)
This case report describes a routine diagnostic left heart catheterisation (coronary angiography, aortography and left ventriculography) procedure at Sultan Qaboos University Hospital, Oman, which was complicated by the development of new asymptomatic, but permanent, left bundle branch block that was observed incidentally towards the end of the procedure. The patient was completely asymptomatic and haemodynamically stable throughout the procedure and afterwards. Urgent investigations, immediately after the procedure, including routine blood, serial cardiac troponin I, serial electrocardiograms, chest X-ray, and urgent echocardiography were normal and failed to show any possible causation of the LBBB. The results of left heart catheterisation showed two vessel coronary artery disease and severe mitral valve regurgitation. After eight days, the patient went on to have coronary artery bypass surgery and mitral valve replacement surgery both of which were successful. To the best of our knowledge, this is the first case report to describe the occurrence of permanent LBBB after left heart catheterisation. This report describes the case and reviews the literature for the incidence and implications of such a complication.